2020
DOI: 10.1037/tra0000918
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an emotional support and mental health response plan for healthcare workers during the COVID-19 pandemic.

Abstract: Center for Child Traumatic Stress Institutions across the world are working to develop initiatives aimed at supporting the well-being of healthcare workers (HCWs) facing the psychological impacts of the novel coronavirus (COVID-19) pandemic. This Commentary identifies risks that HCWs are experiencing, reviews sources of fear and stress, and describes the implementation of a three-tiered model for the provision of emotional support and mental health services for clinical and nonclinical HCWs. The model recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 4 publications
(7 reference statements)
0
51
0
1
Order By: Relevance
“…These findings are in line with those of other studies that found that fear of infecting family members is one of the greatest fears of healthcare professionals and that professionals' sex did not play an essential role in this perception. 27 , 28 , 30 On the other hand, we found that women were more concerned than men about the possibility of infecting patients and coworkers. This finding could be related to the social roles associated with female gender in caring for others 36 as well as with a greater degree of emotional identification and therefore with greater involvement in patients’ physical and emotional well-being.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…These findings are in line with those of other studies that found that fear of infecting family members is one of the greatest fears of healthcare professionals and that professionals' sex did not play an essential role in this perception. 27 , 28 , 30 On the other hand, we found that women were more concerned than men about the possibility of infecting patients and coworkers. This finding could be related to the social roles associated with female gender in caring for others 36 as well as with a greater degree of emotional identification and therefore with greater involvement in patients’ physical and emotional well-being.…”
Section: Discussionmentioning
confidence: 80%
“… 1 , 35 These findings corroborate those of other studies that found that the fear of repercussions for families who have minor children is one of the most common among different healthcare professionals. 6 , 28 , 30 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it would be interesting to evaluate the population once the COVID-19 pandemic finishes, establishing associations within the entire period. Lastly, from another perspective and as a practical application, it has been demonstrated that a cognitive-behaviour intervention and the practice of physical activities may help to obtain higher family, emotional and physical self-concept, as well as a decrease in psychopathological symptoms, in harmful situations in which psychosocial problems appear and there is a detriment of mental health [22,30,80,81].…”
Section: Discussionmentioning
confidence: 99%